On money: A brief intellectual interpretation - Massimo Fornasari (The Journal of European Economic History (JEEH), 2023)
The nature of money continues to perplex us. Over time anthropologists, economists, historians and sociologists have provided various answers to the question "what is money?" Ultimately these answers reflect different and often contradictory approaches to the dynamics of economic systems and especially the dynamics of market economies. But the answers to this question have determined both the reconstruction of certain crucial passages of European economic history, as well as the formulation of targeted economic policies. This paper investigates some of these aspects, juxtaposing the two prevalent orientations, metallists and chartalists. Here we analyse their different theoretical foundations and how each of them directly or indirectly influenced historical research. What emerges is the inadequacy of the position that asserts the neutrality of money. In reality, far from representing a veil, money is an ancient social technology, actually one of man's fundamental social technologies, along with writing and accounting.
Keywords: 330; monetary theory; monetary history; Geldtheorie; Geldgeschichte